Bagaço de maçã úmido como indutor na produção de pectinases por Aspergillus niger - Ramos, Kimberly Costa (My University, 2020)
The by-products of industrial fruits processing can be used as low-cost raw materials aiming to the obtainment of value-added microbial metabolites. However the necessity of pretreatments such as drying and grinding can make the use of these materials operationally and financially unfeasible. In particular, it was evaluated the use of wet apple pomace as an inducer for pectinase production by Aspergillus niger LB-02-SF in solid state cultivation. Different proportions of wet apple pomace (25-100% w/w) and wheat bran (0-75% w/w) were evaluated in the medium composition. Considering the best results obtained, the initial media moisture was varied. A higher enzyme activity was achieved using 25% of wet apple pomace and 75% of wheat bran (D condition). In cultivations with different initial moisture content - D (67%), D1 (62%) and D2 (53%) - the values obtained for maximum enzyme activity were similar, around 60 U/g. Furthermore, the higher enzymatic productivity (0.92 U/g/h) was achieved in condition D, being the peak of activity reached in 72 hours of process. The results indicate the applicability of wet apple pomace as an inducer of A. niger pectinases in solid state cultivation [resumo fornecido pelo autor].
Os subprodutos do processamento industrial de frutas podem ser empregados como matérias-primas de baixo custo para obtenção de metabólitos microbianos de valor agregado. Entretanto, a necessidade de pré-tratamentos, como secagem e moagem, pode inviabilizar operacional e financeiramente o aproveitamento desses materiais. Nesse contexto, foi avaliada a utilização de bagaço de maçã úmido como indutor da produção de pectinases por Aspergillus niger LB-02-SF em cultivo em estado sólido. Foram testadas diferentes proporções de bagaço de maçã úmido (25-100%, m/m) e de farelo de trigo (0-75%, m/m) no meio de cultivo. A partir da melhor proporção definida, foi variada a umidade inicial dos meios. Entre as proporções avaliadas, valor de atividade enzimática superior foi atingido com a utilização de 25% de bagaço de maçã úmido e 75% de farelo de trigo (D). Nos cultivos com diferentes teores de umidade inicial - D (67%), D1 (62%) e D2 (53%) - os valores de máxima atividade enzimática foram semelhantes, cerca de 60 U/gms. Contudo, maior produtividade enzimática (0,92 U/g/h) foi atingida na condição D, com pico de atividade atingido em 72h de processo. Os resultados revelam a aplicabilidade do bagaço de maçã úmido bruto como indutor de pectinases de A. niger em cultivo em estado sólido [resumo fornecido pelo autor].
Keywords: Aspergillus niger; Maçã; Bagaço; Enzimas